Strategic Overview of CRPs: Part II. Value Chains and Seed Systems - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2012)
These think pieces deal with the interface between research and development. The two think pieces provide very useful analysis of the issues where the CRPs can share their common lessons and plan collective strategies and actions, and where some CRPs have specific strengths from which other CRPs can benefit.